Analysis Of the Effect Of E-Accounting And E-Payroll on The Effectiveness Of Internal Control - Herry Wira Wibawa; Hendry Muhammad Ali; Dewi Nari Ratih Permada; Verdi Yasin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Purpose of this study is to determine the effect of e-accounting and e-payroll on the effectiveness of internal control partially or simultaneously. The population of this study was 57 employees, and a sample of 57 people was assigned. The sampling technique was carried out by method sampling saturated or census. The data collection technique was carried out using a research instrument in the form of a questionnaire. The collected data was processed with the IBM Statistics SPSS application using the statistical method of multiple regression analysis. The results of this study indicate that partially there is a significant effect between e-accounting on the effectiveness of internal control and e-payroll on the effectiveness of internal control. Simultaneously there is an influence between e-accounting and e-payroll on the effectiveness of internal control. The independent variables, namely e-accounting and e-payroll, affect the dependent variable or the effectiveness of internal control by 92.5%, and 7.5% is influenced by other variables outside this study..